REMUNERATION SYSTEMS FOR PRIMARY HEALTH CARE WORKERS - Nusipov Tileuzhan Kairkhanovich; Kurakbayev Kuralbay Kurakbaevich; Imasheva Bayan Imashkyzy (European Research Materials, 2025)
Introduction: In the modern world, human resource development strategies play a key role in strengthening health systems. The effectiveness of the healthcare system directly depends on the quality and motivation of medical personnel. In primary health care, medical professionals play a key role in ensuring timely medical care. The most important tool for increasing motivation and efficiency is a fair and transparent remuneration system. The issue of remuneration of medical workers is relevant all over the world. Aim of the study: to summarize the available literature on the existing systems of remuneration for primary health care workers. Materials and methods: An analytical review of open-access literary sources from the scientific databases PubMed/Medline, Scopus, Web of Science, CyberLeninka over the past 10 years (2014-2024) was conducted. Results: This literature review has identified the main remuneration systems for medical workers, where the goals and objectives of each system are defined. According to scientific evidence, the most commonly used payment systems for paying medical professionals are salary, per capita rate, service fee, pay for results, and mixed or combined payment systems. The necessary WHO recommendations have been established to stimulate the work of medical professionals in the healthcare system. Conclusion: Thus, our analysis of the available literature has shown the existence of various wage systems, where each healthcare provider in different countries chooses the appropriate one for their state in order to encourage medical professionals to provide the highest quality medical care.